1998
DOI: 10.1002/(sici)1096-9861(19980330)393:1<118::aid-cne11>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Transient molecular visualization of ocular dominance columns (ODCs) in normal adult marmosets despite the desegregated termination of the retino-geniculo-cortical pathways

Abstract: The activity-dependent immediate early gene protein Krox-24, expressed in the neocortex at high basal levels, decreases rapidly upon neuronal deactivation (Chaudhuri et al. [1995] Vis. Neurosci. 12:35-50). In infant marmosets, as in most primates, the geniculo-cortical terminations segregate into eye-specific anatomical ocular dominance columns (ODCs), which disappear, however, during adolescence (Spatz [1989] Brain Res. 488:376-380), resulting in balanced inputs from the two eyes (Sengpiel et al. [1996] Vis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…Consistent with the previous report (Markstahler et al, 1998), the active-eye columns were visualized by ISH for ZIF268 in the marmoset visual cortex (Figure 2A). Similar stripe patterns were observed for two other IEGs, ARC and c-FOS , as well (Figures 2B,C).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with the previous report (Markstahler et al, 1998), the active-eye columns were visualized by ISH for ZIF268 in the marmoset visual cortex (Figure 2A). Similar stripe patterns were observed for two other IEGs, ARC and c-FOS , as well (Figures 2B,C).…”
Section: Resultssupporting
confidence: 92%
“…A previous study showed the narrow (thin) pale-staining rim below the strong ZIF268 signals in layer IVC in marmoset V1 (Markstahler et al, 1998). From its position, this sublayer is considered as equivalent to the blank sublayer of ZIF268 mRNA observed at 140 min after light induction (showed by the filled star in Figure 5D).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Early work suggested that marmosets lack ODCs in adulthood (Spatz, 1979, 1989; DeBruyn and Casagrande, 1981), although they can be transiently induced by silencing the input from one eye (Markstahler et al, 1998). Functional measurements in adults also suggest weak segregation of ocular dominance (Sengpiel et al, 1996; Roe et al, 2005).…”
Section: Primary Visual Cortex (V1)mentioning
confidence: 99%